ANALISIS GAYA BAHASA KUMPULAN PUISI TENTANG RINDU PLUS KARYA ROMANTIS DAN KRITIS ROCKY GERUNG KARYA YALIZAR RAHAYU DAN PEMANFAATANYA SEBAGAI MODUL AJAR PEMBELAJARAN SASTRA DI SMA: Penelitian deskriptif kualitatif - Artono; Muji Zain Naufal; Ade Hasanudin (STKIP Subang, 2025)
In this study, the researcher analyzed the language style of poetry about longing plus romantic and critical works of Rocky Gerung by Yalizar Rahayu, this study was used based on field observations conducted by researchers and several scientific journals. The purpose of this study is to describe the results of the analysis of figures of speech in the poetry collection About Longing Plus Romantic and Critical Works of Rocky Gerung by Yalizar Rahayau. to describe the use of the results of the analysis of language style (figures of speech) in the poetry collection about Longing Plus Romantic and Critical Works of Rocky Gerung by Yalizar Rahayau used as a learning module. Researchers use descriptive research that aims to describe situations or events based on word descriptions. The data collected are in the form of words, images, and not numbers. Based on the data analysis in this study, it can be concluded that of the 5 poems analyzed, all poems contain figurative language. Comparative figurative language found 7 types of figurative language, namely hyperbole, metaphor, personification, aphorism, simile, allegory, and association. Contrasting figurative language found 3 types of figurative language, namely paradox, antithesis, and hyperbole. Language style two types of repetition were found: anaphora and alliteration. The results of this study suggest that readers can use this research to deepen their understanding and deepen their understanding of the language styles found in literary works. This research serves as a reference for readers to introduce and preserve poetry as a meaningful work of the nation's children. The results of this study are also useful for poetry teaching in schools.